Species-Discriminating Diagnostic PCR, Ribosomal Intergenic Spacer-Based Single-Marker Taxonomy and Cryptic Descriptions of the Fungal Entomopathogens Metarhizium hybridum and Metarhizium parapingshaense - Schuster, Christina (2026)
(1) Background: Potentially arthropod-pathogenic and plant-associated Metarhizium fungi are of high interest for basic research, biological pest control and plant growth promotion. Unambiguous species delineation enabling the taxonomic assignment of new isolates and the identification of new Metarhizium species is of crucial importance for both research and application. Recently, the new species Metarhizium hybridum and Metarhizium parapingshaense were introduced on the basis of phylogenomic studies. (2) Methods: Neighbor- joining and Bayesian inference-based phylogenetic reconstruction of ribosomal intergenic spacer (rIGS) sequences were used to critically evaluate new species introductions. A species-discriminating diagnostic PCR tool for Metarhizium was adapted to M. hybridum and M. parapingshaense. GenBank database mining was performed to identify cryptic descriptions of the new species. (3) Results: The introduction of M. hybridum and M. parapingshaense was corroborated by rIGS sequence comparison. Data mining revealed cryptic first descriptions of M. hybridum from Canada, China, Colombia, Costa Rica, Cuba, Honduras, Mexico, New Zealand, the USA and the Philippines, and of M. parapingshaense from China, India, Japan, the Philippines and South Korea. (4) Conclusions: Results support the reliability of rIGS as a single taxonomic marker for species-level identification of Metarhizium fungi. Species-discriminating diagnostic PCR was successfully adapted to enable the sequencing-independent identification of the confirmed new species M. hybridum and M. parapingshaense.